Promoting Ksatria Bela Negara comic through the Webtoon for the prevention and control Covid-19 - Anggraeni, Leni; Darmawan, Cecep; Tanshzil, Sri Wahyuni; Jubaedah, Edah (Universitas Negeri Yogyakarta, 2021)
During the Covid-19 pandemic, everyone must be at home and keep a distance using a mask. The spread massively. It becomes the basis for all stakeholders to find solutions, both in the form of preventive (prevention) and curative (cure). One of the strategic educational media used to prevent and overcome covid-19 for the current generation of digital natives is through digital comics or webtoons. Comics in digital form has many advantages over printed comics. Based on this, the research aims to find out how the impact of the promotion of the National Defense Knight Comics through the Webtoon as an educational medium for preventing and controlling Covid-19 for the community. The method used is Research and Development (R&D) using the Waterfall development model. The results of this review show that promoting comics of state defense knights through webtoons can become a medium of persuasion for education on preventing and overcoming Covid-19. The innovative education offered by the knight Bela Negara comic designs webtoon readers to be closer to the story and characters because it is more humane, so that they are able to show the effects in the form of responses, both cognitive (knowledge development), affective (through positive attitudes) and connective (action as the results of stimulating positive attitudes) related to the prevention and handling of covid-19.